Role of PTX3 in corneal epithelial innate immunity against Aspergillus fumigatus infection. (February 2018) - Zhang, Jie; Zhao, Guiqiu; Lin, Jing; Che, Chengye; Li, Cui; Jiang, Nan; Hu, Liting; Wang, Qian
Abstract: Pentraxin3 (PTX3), a member of long pentraxin family, plays a non-redundant role in human humoral innate immunity. However, whether PTX3 is expressed by corneal epithelial cells and its role during corneal fungi infection has not yet been investigated. To identify the presence of PTX3 in cornea, the possible mechanisms involved in its expression, and also the effects on corneal anti-fungi innate immune response, clinic human corneal tissues and cultured human corneal epithelial cells (HCECs) were resorted. PTX3 mRNA and protein were detected in corneal samples and cultured HCECs, which was significantly up-regulated after exposing to Aspergillus fumigatus ( A. fumigatus ). Pretreated with specific inhibitors, only Syk contributed to the regulation of PTX3 expression in Dectin-1/Syk signal axis. Furthermore, among the MAPK members (p38 MAPK, ERK1/2 and JNK), only ERK1/2 and JNK were responsible for A. fumigatus induced PTX3 production. Blocking of endogenous PTX3 by siRNA down-regulated the production of IL-1β at both mRNA and protein levels. Meanwhile, blocking of PTX3 also inhibited the phosphorylation of ERK1/2 and JNK, but not p38 MAPK. These findings demonstrate that PTX3 is expressed in human corneal epithelial cells and Syk, ERK1/2, JNK signaling pathways play an important role in the regulation of PTX3 induction. PTX3 plays a proinflammatory role in corneal epithelial anti-fungi immune response by affecting the production of IL-1β and activation of some proinflammatory signaling pathways (ERK1/2 and JNK). Highlights: PTX3 is expressed in corneal epithelial cells and up-regulated by Aspergillus fumigatus stimulation. PTX3 expression in corneal epithelial cells was Syk, ERK1/2 and JNK dependent. PTX3 plays a proinflammatory role during corneal anti-fungi immune response.